Assessing an ovarian reserve and risk factors for premature ovarian failure as part of pre-abortion counseling for women under 40 planning to terminate own first pregnancy - L. V. Tkachenko; I. A. Gritsenko; K. Yu. Tikhaeva; N. I. Sviridova; I. S. Gavrilova; V. A. Dolgova (Акушерство, гинекология и репродукция, 2023)
Introduction. The problem of artificial pregnancy termination is of global importance. Any woman faced with the problem of reproductive choice is vulnerable, needs both to be advised by an obstetrician-gynecologist and high-quality psychological support. At the stage of pre-abortion counseling, it seems possible to influence a decision to keep pregnancy by identifying risk factors for premature ovarian failure (РОF), laboratory and ultrasound criteria for reducing ovarian reserve (OR).Aim: optimization of the pre-abortion counseling algorithm by introducing an assessment of OR. Materials and Methods. A retrospective study was conducted, which included 58 women under 40 living in the Volgograd region and planning to terminate own first pregnancy. In order to identify factors of early decrease in OR, anamnestic data of patients were evaluated. A comprehensive assessment of the main OR parameters was performed by assessing blood serum level of anti-Mullerian hormone (AMH), follicle-stimulating hormone (FSH) and inhibin B, ultrasound counting the number of antral follicles.Results. In the main group of patients, 8 (13.8 %) of the examined patients had a birth weight of about 2800 g, 6 (10.3 %) – with a history of ovarian surgery and ovarian cysts were found after menarche. A relationship was also found between OR laboratory parameters in primigravida and the age of menopause in paired mothers: 2 (3.4 %) – 45 years, 8 (13.8 %) – 48–50 years. According to the diagnostic results, 10 (17.2%) patients showed a decrease in ОR and 48 (82.8%) patients had a normal OR. Taking into account the data obtained, a modified project of pre-abortion counseling was developed for the first time devoted to РОF.Conclusion. The modified section of pre-abortion counseling takes into account the specifics of maternal OR and can improve quality of medical care for women planning to terminate own pregnancy due to more comprehensive information as well as affect the awareness of reproductive plans in the future.